2011
DOI: 10.1095/biolreprod.110.088211
|View full text |Cite
|
Sign up to set email alerts
|

PTGS2-Related PGE2 Affects Oocyte MAPK Phosphorylation and Meiosis Progression in Cattle: Late Effects on Early Embryonic Development

Abstract: During the periovulatory period, the induction of prostaglandin G/H synthase-2 (PTGS2) expression in cumulus cells and associated prostaglandin E2 (PGE2) production are implicated in the terminal differentiation of the cumulus-oocyte complex. During the present study, the effects of the PTGS2/PGE2 pathway on the developmental competence of bovine oocytes were investigated using an in vitro model of maturation, fertilization, and early embryonic development. The specific inhibition of PTGS2 activity with NS-398… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 45 publications
5
42
1
3
Order By: Relevance
“…Therefore, the increase in MI is due to a delay in nuclear maturation without compromising the developmental competence of the oocyte. This is in agreement with the previous data from Nuttinck et al (2011) who found that PTGS2 inhibition significantly increased oocytes at MI after 22 h and also showed that NS398 decreased embryo output rates on day 6 post fertilization but not on day 7. They also showed that total blastomere number was significantly lower in embryos obtained after PTGS2 inhibition, while no effect on total cell number in the blastocyst on day 7 could be seen in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the increase in MI is due to a delay in nuclear maturation without compromising the developmental competence of the oocyte. This is in agreement with the previous data from Nuttinck et al (2011) who found that PTGS2 inhibition significantly increased oocytes at MI after 22 h and also showed that NS398 decreased embryo output rates on day 6 post fertilization but not on day 7. They also showed that total blastomere number was significantly lower in embryos obtained after PTGS2 inhibition, while no effect on total cell number in the blastocyst on day 7 could be seen in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that PTGS2-derived PGE 2 plays an important role in cumulus cell expansion and oocyte maturation in rodents (Eppig, 1981;Hizaki et al, 1999;Lim et al, 1997;Takahashi et al, 2006) but with fewer studies in cattle (Nuttinck et al, 2011), the role of PGE 2 in oocyte maturation is less characterized and it is not clear if PGE 2 can be used as an additive to improve oocyte competence. The present study examined the expression of genes involved in the synthesis of PGE 2 and PGF 2a in bovine COC and the role of exogenous PGE 2 supplementation during bovine oocyte maturation in the presence or absence of Gn.…”
Section: Introductionmentioning
confidence: 99%
“…PTGER, the prostaglandin E (PGE) receptor, is expressed in oocytes and CCs. PGE-PTGER signaling regulates CCs expansion and reorganization, which is required for successful sperm attraction, capture, and penetration52. In our study, the expression of both PTGER2 and PTGER4 was higher in PCOS GV CCs and enhanced the proliferation of CCs.…”
Section: Discussionsupporting
confidence: 47%
“…Blocking prostaglandins (i.e. PTGS2) decreases cumulus expansion and slows the rate of embryo development in the in vitro bovine system (Nuttinck et al 2011). By contrast, higher PTGS2 mRNA levels occur in the cumulus cells of human oocytes expressing the highest developmental capacity (Gebhardt et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PTGS2 is positively regulated by FSH, epidermal growth factor (EGF; Joyce et al 2001, Shimada et al 2006, and oocyte-secreted factors (Elvin et al 2000, Joyce et al 2001, Dragovic et al 2007. Because inhibiting PTGS2 during IVM can decrease cumulus expansion, oocyte maturation, and ultimately embryo production (Nuttinck et al 2011), we predicted that a seasonal difference in the production of resulting enzyme may indicate altered FSH function. EGF can promote oocyte maturation (Farin et al 2007, Hatoya et al 2009, Uhm et al 2010 and is necessary for FSH-induced meiotic resumption (Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%